2019
DOI: 10.22319/rmcp.v10i1.4655
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sheep social hierarchy on feeding behavior and parasite load in silvopastoral and grass monoculture grazing systems

Abstract: Para determinar la relación entre el nivel jerárquico, preferencias por forraje y parasitismo de ovinos en dos sistemas de pastoreo (sistema silvopastoril: SSP y monocultivo de pasto estrella: PE). Se utilizaron 11 ovinos de la raza pelibuey mantenidos en pastoreo diurno, a los cuales se les aplicó pruebas de jerarquía social para obtener el índice de dominancia, pruebas de selectividad de especies vegetales forrajeras (C. nlemfuensis, L. leucocephala, G. sepium, G. ulmifolia y H. rosa-sinensis), análisis para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…For example, dominant individuals tend to be more assertive, confident, and proactive ( Blanchard et al, 1988 ; Salonen et al, 2022 ), while submissive individuals are often more anxious, passive, and reactive ( Catarino et al, 2014 ; Zaffar and Arshad, 2020 ). In addition, social hierarchy can shape individual behavior and physiology ( Schmid Mast, 2010 ; Flota-Bañuelos et al, 2019 ) including stress responses ( Knight and Mehta, 2017 ; Karamihalev et al, 2020 ), brain activity ( Breton et al, 2014 ; Williamson et al, 2019a ), and gene expression ( Pohorecky et al, 2004 ; Horii et al, 2017 ; Lea et al, 2018 ; Williamson et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dominant individuals tend to be more assertive, confident, and proactive ( Blanchard et al, 1988 ; Salonen et al, 2022 ), while submissive individuals are often more anxious, passive, and reactive ( Catarino et al, 2014 ; Zaffar and Arshad, 2020 ). In addition, social hierarchy can shape individual behavior and physiology ( Schmid Mast, 2010 ; Flota-Bañuelos et al, 2019 ) including stress responses ( Knight and Mehta, 2017 ; Karamihalev et al, 2020 ), brain activity ( Breton et al, 2014 ; Williamson et al, 2019a ), and gene expression ( Pohorecky et al, 2004 ; Horii et al, 2017 ; Lea et al, 2018 ; Williamson et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…In the herds from the municipality of Hecelchakán there was coloring of the mucosae (FAMACHA ® ) with 2.5 (between light red and pink) (F8.758, P0.000016) (Table 2); meanwhile, in the herds of the rest of the municipalities studied, the coloring of the mucosae is closer to the range 3 (pink) or limit (light pink), considered as intermediate value where the animal can be considered both anemic and non-anemic (Zárate et al, 2017). The sheep with best coloring of the ocular mucosae presented better body condition (r0.323408, P0.05); this situation is because the sheep from the production units of the municipality of Hecelchakán are supplemented with commercial concentrate feed and fodder from shrub and tree species, which allow varying the diet, covering their requirements (Provenza, 1996), and in addition they promote the capacity to resist high parasite loads (Flota-Bañuelos et al, 2019).…”
Section: Prevalence Of Gastrointestinal Parasites In Sheepmentioning
confidence: 99%
“…In Yucatán and Tabasco, Mexico, studies have been conducted on the prevalence and loads of gastrointestinal parasites in sheep (González-Garduño et al, 2011;López-Ruvalcaba et al, 2013), and high prevalence of larvae of Haemonchus contortus (68,9%), followed by Trichostrongylus colubriformis (30.9%) and Cooperia curticei (0.6%) (Zaragoza-Vera et al, 2019) were reported until 2019. Likewise, studies have been conducted for the detection of anthelminthic resistance (Torres-Acosta et al, 2012) through the analysis of immunological parameters (Alvarado-Alvarado et al, 2017) and through the level of social hierarchy on the parasite load (Flota-Bañuelos et al, 2019). Within the strategies of prevention or control, the following have been implemented: use of FAMACHA © (Soto- Barrientos et al, 2018), copper oxide needles (Galindo-Barbosa et al, 2011), selective removal of parasites (Medina-Pérez et al, 2015), use of plants with presence of secondary metabolites (Herrera-Manzanilla et al, 2017;Sepúlveda-Vázquez et al, 2018), or residues of Coffea arabica (Ortiz-Campos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Como resultado de las pruebas etológicas (prueba de aislamiento y prueba de contacto con el humano), solo un individuo presento respuesta negativa en la aplicación, esto debido al alto nivel de jerarquización presente en el grupo y a su condición de animal joven, recién llegado al grupo. Eso ratifica, lo expuesto por [46], [47] donde se menciona que los caprinos, son esencialmente una especie gregaria que basan sus estrategias de adaptación y sobrevivencia en una intensa vida social, encaminada a la vida en rebaño, esto afecta el comportamiento productivo y reproductivos de los animales [48]; [49].…”
unclassified